The Impact of Pension Reform on Employment, Retirement and Disability Insurance Claims - Erik Hernaes; Simen Markussen; John Piggott; Knut Røed (Institute of Labor Economics (IZA), 2023)
We evaluate a comprehensive reform of Norwegian early retirement institutions in 2011 through the lens of a parsimonious random utility choice model. The reform radically changed work incentives and/or pension access-age for some (but not all) workers. We find that improved work incentives caused employment to rise considerably, at the expense of both early retirement and exits through disability insurance. Lower access-age to own pension funds caused a small increase in employment and a large drop in disability program participation. Properly designed pension reforms thus need to take the interplay between old age pension and disability insurance programs into account.
Keywords: H55; J22; 330; pension reform; disability insurance; program substitution